Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd010427.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) in non surgical wounds

Abstract: We found no trials comparing the use of antibiotics with no antibiotic for treating MRSA-colonised non-surgical wounds and therefore can draw no conclusions for this population. In the trials that compared different antibiotics for treating MRSA-infected non surgical wounds, there was no evidence that any one antibiotic was better than the others. Further well-designed RCTs are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Amongst antimicrobials for which in vitro testing has shown susceptibility of a particular isolate, the choice will be based on clinical characteristics. No single drug has been shown to be better than another in a Cochrane review on antibiotic treatment of MRSA wounds in humans . If the initial laboratory report includes susceptibilities to drugs that are available and licensed for the species, these should be considered first.…”
Section: Therapeutic Considerations For Mrs Infectionsmentioning
confidence: 99%
“…Amongst antimicrobials for which in vitro testing has shown susceptibility of a particular isolate, the choice will be based on clinical characteristics. No single drug has been shown to be better than another in a Cochrane review on antibiotic treatment of MRSA wounds in humans . If the initial laboratory report includes susceptibilities to drugs that are available and licensed for the species, these should be considered first.…”
Section: Therapeutic Considerations For Mrs Infectionsmentioning
confidence: 99%
“…There have been numerous meta-analyses to compare the efficacy of the aforementioned agents in MRSA infection. Four meta-analyses are unusual in that they have assessed all possible treatment options [106][107][108][109], although only one study [107] examined all MRSA infection types (as opposed to MRSA cSSTIs). This latter (network metaanalysis) study identified 24 RCTs (17 for cSSTI and 10 for HAP/VAP) comparing one of six antibiotics with vancomycin.…”
Section: Mrsamentioning
confidence: 99%
“…This Gram‐positive bacterium is likewise well‐known for biofilm formation in diverse infections involving artificial or biological surfaces . Methicillin‐resistant S. aureus (MRSA) is an infamous contributor to the global antibiotic resistance crisis due to its propensity to carry multidrug resistance (MDR) . The prevalence of MRSA in chronic wounds is 7–30% .…”
mentioning
confidence: 99%
“…2,19 Methicillin-resistant S. aureus (MRSA) is an infamous contributor to the global antibiotic resistance crisis due to its propensity to carry multidrug resistance (MDR). 20,21 The prevalence of MRSA in chronic wounds is 7-30%. 21 By forming biofilms in chronic wounds, MRSA can combine targeted MDR with the general antimicrobial tolerance and immune protection of biofilms to create a challenging therapeutic situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation